THE INFLUENCE OF THE DISCOVERY LEARNING MODEL ON STUDENTS' COLLABORATION ABILITY AT SMAN 2 PADANG - Hastuti, Shinta Fuji (Department of Physics Universitas Negeri Padang, 2024)
This research aims to see whether there is an influence of the discovery learning model on the collaboration abilities of students at SMAN 2 Padang. The research method used was quasi-experimental with a posttest control design. Sampling in this study used purposive sampling and class XI phase F (physics 5) was obtained as the experimental class and class XI phase F (physics 2) was the control class. Data on students' collaboration abilities was taken using an observation sheet assessing students' collaboration abilities which was analyzed descriptively. To see the magnitude of the influence of the discovery learning model on students' collaboration abilities, effect size calculations are used. The results of the research showed that the average value of collaboration ability of students in the experimental class was (68.19 ± 2.49) with good criteria, whereas the average value of collaboration ability of students in the control class was (63.43 ± 2.45) with good criteria. The magnitude of the influence of the discover learning model on students' collaboration abilities is obtained from an effect size index of 1.9 and has a high category in improving students' collaboration abilities. The discovery learning model can be concluded to have an influence on students' collaboration abilities.